The video guide for SPSS Version 13.0 - Saviano, Mark S.; Thomson Wodsworth ([S.l. : s.n.)
This video guide for SPSS makes it easy to learn how to use SPSS statistical software
Editor , Vicki Knight
System requirement : Windows Pentium computer drive ; Windows 98/2000/XP (not NT) ; Pentium II 233 MHz ; 32 MB RAM (64 MB Recommended) ; Mac OS 8.6 or later ; Power PC Processor or later ; 64 MB RAM ; 800 x 600 , lb-Bit High - Color Display ; 16 Bit Sound Card ; Speaker or Headphones ; 8 x CD-ROM
Keywords: SPSS (Computer program); SPSS for Windows